2021
DOI: 10.3390/met11020270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cooling Time on the Microstructural Evolution and Mechanical Performance of a Double Pulse Resistance Spot Welded Medium-Mn Steel

Abstract: In the present work, the influence of the cooling time on the mechanical performance, hardness, and microstructural features of a double pulse resistance spot welded medium-Mn steel are investigated. Curves of the electrical resistance throughout the welding revealed that the cooling time strongly influences the heat generation during the second pulse. A second pulse after a short cooling time re-melts the center, and heat treats the edge of the primary fusion zone. This desired in-process heat treatment leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…A CE value of >0.45-0.5 has a 'poor' weldability [65] and will require special welding processes. Unfortunately, most medium Mn steels have a high CE and initial studies have found the resistance spot weldability of medium Mn steels to be poor with very low cross tension strengths [207][208][209]. A cross tension strength test is where two strips of steel are arranged in a '+' shape and spot welded together at the overlap.…”
Section: Welding and Liquid Metal Embrittlementmentioning
confidence: 99%
See 1 more Smart Citation
“…A CE value of >0.45-0.5 has a 'poor' weldability [65] and will require special welding processes. Unfortunately, most medium Mn steels have a high CE and initial studies have found the resistance spot weldability of medium Mn steels to be poor with very low cross tension strengths [207][208][209]. A cross tension strength test is where two strips of steel are arranged in a '+' shape and spot welded together at the overlap.…”
Section: Welding and Liquid Metal Embrittlementmentioning
confidence: 99%
“…The predominant failure mode was found to be interfacial failure which is undesirable. Mn segregation to dendrite boundaries in the FZ also creates a local region with high CE and brittleness [207,209].…”
Section: Welding and Liquid Metal Embrittlementmentioning
confidence: 99%
“…For example, Fig. 1 STS values of RSWed high-to ultra-high strength steels in similar [18, and dissimilar [12,23,25,36,38,43,50,78,79,82,87,96,98,100,101,115,119,125, joint configurations for the welding of a R m = 1500 MPa steel the same STS is required for the joint as for a R m = 1200 MPa steel grade (see also in Figs. 2 and 3).…”
Section: Equations To Predict the Shear Tension Strength 21 Different Sts Prediction Models Of The Literaturementioning
confidence: 99%
“…Multiple welding current pulses also act as a post weld heat treatment (PWHT). Stadler et al [18] have found that the second welding current pulse remelted the center of the weld nugget of a 0.1 C, 6.4 Mn, 0.6 Si (wt%) medium Mn-steel, leading to a recrystallization and homogenization of the initial weld microstructure, thus improving the mechanical properties. For the optimization of welding process parameters design of experiments (DoE) methods have widely been used in RSW.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the modification of the microstructure of the FZ, for example, with a second pulse that acts as an in-process heat treatment, represents a well-documented approach to improve their mechanical performance [ 13 , 14 , 15 , 16 , 17 , 18 ]. This approach has already been successfully adopted to improve the properties of the medium-Mn steel investigated in the present work [ 19 ].…”
Section: Introductionmentioning
confidence: 99%